Glycation of bovine serum albumin by ascorbate in vitro: Possible contribution of the ascorbyl radical? - Sadowska-Bartosz, Izabela (Redox Biol, 2015)
Ascorbic acid (AA) has been reported to be both pro-and antiglycating agent. In vitro, mainly proglycating effects of AA have been observed. We studied the glycation of bovine serum albumin (BSA) induced by AA in vitro. BSA glycation was accompanied by oxidative modifications, in agreement with the idea of glycoxidation. Glycation was inhibited by antioxidants including polyphenols and accelerated by 2,​2′-​azobis-​2-​methyl-​propanimidamide and superoxide dismutase. Nitroxides, known to oxidize AA, did not inhibit BSA glycation. A good correlation was observed between the steady-state level of the ascorbyl radical in BSA samples incubated with AA and additives and the extent of glycation. On this basis we propose that ascorbyl radical, in addition to further products of AA oxidation, may initiate protein glycation.